Effect of Volatile Fatty Acid Concentration on Anaerobic Degradation Rate from Field Anaerobic Digestion Facilities Treating Food Waste Leachate in South Korea - Dong-Jin Lee; Su-Young Lee; Ji-Su Bae; Jung-Gu Kang; Ki-Heon Kim; Sung-Su Rhee; Jong-Hwan Park; Ju-Sik Cho; Jin Chung; Dong-Cheol Seo (Journal of Chemistry)
The purpose of this study was to investigate the effect of volatile fatty acid concentration on anaerobic degradation rate of food waste leachate in the anaerobic digestion facilities. The anaerobic digestion facilities treating food waste leachate (FWL), codigestion with food leachate and animal manure (A-MIX), and codigestion with food waste leachate and sewage sludge (S-MIX) were selected for this study. In accordance with the regulation under Wastes Control Act in South Korea, the guideline of volatile solid removal rate for anaerobic digestion facility is set as 65% for anaerobic degradation efficiency. Highest volatile solids removal rates were achieved from FWL (63.5%) than A-MIX (56.4%) and S-MIX (41.2%). Four out of eight FWLs met the guidelines. The concentration of volatile fatty acids, therefore, was analyzed to determine the relationship with volatile solid removal rate. The results showed that, in order to meet the Korean guideline of 65% volatile solid removal rate, volatile fatty acid concentrations should remain below 4,000 mg/L on the field anaerobic digestion facilities treating FWL. Volatile fatty acid concentrations should be used along with others as an operational parameter to control and manage the anaerobic digestion process.